An Optimized Equivalent Source Modeling for the Evaluation of Time Harmonic Radiated Fields from Electrical Machines and Drives - Barzegaran, M. R.; Sarikhani, Ali; Mohammed , Osama A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A model for electrical machines useful for radiated electromagnetic field studies in a multi-source environment is proposed. The various aspects of electromagnetic signature are considered. This model was created from a representative rectangular prism carrying a set of unbalanced currents in its branches. The geometry and the currents of the equivalent model were calculated based upon a genetic algorithm-based particle swarm optimization process taking into consideration the actual size and the operating conditions of the drive system being studied. The electric field was chosen as the objective function, which is the main element of the optimization. The simulated results show acceptable accuracy and excellent simulation time as compared to the full 3D FE model of the actual machine. Various types of signature studies of the model were conducted. This included stationary and time analysis in addition to the effect of rotation of the machine. For verification, we utilized two machines in a connected system to study and compare the results with their actual model. The results show satisfactory accuracy. The practical implication of this effort is in the fact that, with this equivalent model, we can evaluate radiation and stray effects for EMC evaluation at the design stage.